TRAVEL AND TOUR ENTREPRENEURE AND THE TOURISM IN THE ANDAMAN AND NICOBAR ISLANDS-A CORRELATION ANALYSIS - ANITHA, G. (International Journal of Psychosocial Rehabilitation, 2020)
Andaman and Nicobar Islands are very rich in resources of which only a few of the resources have been exploited and plenty of resources are yet to be exploited. Both Andaman and Nicobar Administration and Government of India have been announcing much number of incentives, subsidies etc., but still the primary sector and secondary sector do not increase their growth. So tourism is the only hope of these islands. Number of tourists has been increasing every year. The travel & tour entrepreneurs are doing the business of travel agency and tour operations. Some travel agents and tour operators are shining and some are closing their business. No tourism means, no business of the tour operations and travel agency. The growth of the business of the tour operations and travel agency in terms of the number of tour operators and travel agents fully depends on the growth of the tourism in terms of the number of the tourists both the domestic as well as the forging arrived into these islands. Attempts are made to trace the growth of the business of the tour operations and travel agency. Hence tourism is the basis of the growth of the business of the tour operations and travel agency. To find out the relationship between the tourism industry, travel agent, and tour operators, a correlation analysis has been done the results are calculated. Based on the findings, detailed study and the identified problems, the suggestions are made for the better management and overall growth and development of the business of travel agency &tour operations in the Andaman and Nicobar Islands. If a strategy for the travel agency & tour operations is formulated with the new structural and office manual in the light of the suggestions given, and the same is implemented very carefully, it is strongly believed that the business of the travel agency &tour operations will be improved and the same will attract more tourists into these islands.